SIRAH NABAWIYYAH SEBAGAI PERJALANAN TASYR’I (Sebuah Pendekatan Etnografis di Indonesia) - Fabian Fadhly Jambak (Fakultas Agama Islam Universitas Muhammadiyah Bandung, 2020)
The journey of life of the Messenger of Allah influences and forms the Shari’a. Ethnography in the Arabian peninsula (especially Mecca and Medina) influenced the development of Islam in the time of the Prophet, especially Mecca with trade culture and Medina culture agriculture.The Shari'a is influenced by the ethnographic situation in the Arabian peninsula, especially in the holy cities of the Islamic Community, namely Mecca and Medina. Ethnography can influence the development of Islam in the time of the Prophet, especially the Mecca that developed form exchanges of information by traders while the Islamic Medina developed from areas that were culturally derived from agricultural societies. The uniqueness of ethnography and his life’s journey refer to tashri (sharia) in terms of interpretation. Ethnography also influences the growth and development of Islam in Indonesia, which makes Islam acculturate with local culture.This paper is put forward as an effort to show the sirah nabawiyah (the journey of the Prophet's life) as one aspect of sharia formation, influenced by various factors in the spread, growth and development both in the Mecca and Madinah regions, as centers of Islamic teachings and Indonesia which has social differences , cultural, political and economic. The method put forward in this paper is the historical method, with the specification of a library research approach that refers to primary and secondary sources.Ethnography is one of the factors that can influence religious teachings to spread, grow and develop, a reality that also takes place on Islamic teachings. The teachings are influenced by the conditions of Mecca and Medina in shaping the law (tasyr’i). The teachings of Islam in Indonesia are spread and developed and grow sourced from the commercial activities carried out by the Arabian Peninsula in the 7th century AD, but trade does not dwarf the agricultural community that simultaneously embraces Islam, which at the same time also the community of agricultural communities trade with the spreaders of Islam in the Coast region.Keywords: Ethnography, Indonesia, Nabawiyyah, Sirah, Tasyri'